Using video to promote empathy, reduce xenophobia, and illustrate concepts in the study of international migration. (9th May 2017) - Germano, Roy
Abstract: Documentary films and nonfiction videos can go a long way toward enriching courses on international migration by helping students visualize concepts, places, and situations they may have difficulty imagining from written and oral descriptions alone. The vivid portrayals offered by films and videos can also help students empathize with and better understand people they may never come into contact with in their daily lives. In this essay, I will discuss some of the films and videos that I find particularly useful for illustrating concepts and perspectives in the study of migration. In selecting these videos, I am interested in demonstrating that migrants are active agents who are motivated to go abroad for clear social, economic, and political reasons, that they are people who solve problems and overcome challenges, and that many migrants make important contributions to their origin countries and destination countries. I am furthermore interested in showing films and videos that provide a window into some of the challenges and complexities involved with immigration policymaking.